Pharmaceutical sales and marketing as a future career for pharmacy students in Iraq: perception and barriers - Ahmad Kadhum; Mohammed D. Al-Rekabi; Furqan Hashim (Iraqi Journal of Pharmaceutical Sciences, 2023)
The exposure of pharmacy students to fieldwork experience throughout the early stages of their education would assist prepare them for their future career. Many students feel working in community pharmacies does not give a profitable wage when compared to other opportunities. which might influence them to choose the promotional pharmaceutical field. This study aims to examine students' perceptions of the pharmaceutical promotional sector as a potential future profession as well as the obstacles they face. This is a cross-sectional study targeting students of pharmacy in Iraq through an online questionnaire to assess students' perceptions. The perceptions were evaluated to determine the influencing factors. The greatest percentage of students work for improving their skills and for saving money for the future. Concerning the barriers that students face in pursuing a career in pharmaceutical marketing, the existence of unethical actions, as well as a lack of needed skills and knowledge, were cited as barriers by a greater percentage of respondents. In conclusion, generally, there is a favorable view of working in this industry and there is an apparent need for colleges to focus more on the aspects of this career.